PENGEMBANGAN MEDIA BELAJAR ENGLISH FOR CHILDREN (EFC) DENGAN MEMANFAATKAN LIMBAH INDUSTRI GARMEN - Suharto, G; Supriyanti, Nury; Jamilah, Jamilah; Purnawan, Ari (Universitas Negeri Yogyakarta, 2004)
This workshop is aimed at providing knowledge and skills in':. 5g· ning classroom activities, creating and developing learning media from ent waste, and its implementation in the teaching of English for ;,' ren by kindergarten teachers in the Subdistrict of Kalasan, Sleman. egency, Yogyakarta Special Territory.The presentation method includes lecturing, demonstrating, and;::-a tising. Lecturing was employed in presenting the theoretical and literary.e 'iews on teaching children, and in seeking for new alternatives to support:. teachers' creativity in developing the learning media. Demonstrating was conducted in designing classroom activities and lesson units, making media zppropriate for the classroom activities,and managing the teaching-leming. ocess with the focus on the optimal use of the media. The teaching practice.: at was then carried out by the participants included making lesson units.or the classroom activities, creating learning media, and carrying out the.eaching-learning process in the form of micro teaching.This workshop resulted in the improvement of knowledge about new ends in English teaching, the improvement in the skills of designing lesson units and creating learning media, the improvement in the teaching of English using the media, and the eleven sets of media model for theteaching of English using garment waste of various kinds.Key words: English/or children, media